Health sector challenges and responses beyond the Alma-Ata Declaration : a Caribbean perspective - Mullings, Jasneth (2007)
Looks at the early beginnings of primary health care in the Caribbean; Alma-Ata and the Caribbean primary health care strategy; the Caribbean Cooperation in Health concept; emerging issues : 1980 to present; challenges and limitations; and, health sector reponses to the goal of Health for All.